Penerapan Teknologi IoT dan Ragam Sensor Dalam Sistem Monitoring Gelombang Laut sebagai Peringatan Dini - Hadad, Sitna Hajar; Safi, Mudar; Turuy, Seh; Rumaf, Nurdin; Ismail, Risandi J (Building of Informatics, Technology and Science (BITS), 2024)
North Maluku has an archipelago so that community activities are mostly related to the sea, such as fishermen and people who use sea routes as a mode of transportation. Uncertain weather conditions resulting in heavy rainfall and high sea waves can threaten the safety of the community, especially the fishing community and people who use sea transportation modes. As happened some time ago, namely the sinking of KM Cahaya Arafa. KM Cahaya Arafa sank because it was hit by high sea waves so that it had an accident, namely drowning in the waters of Tokaka Village, South Halmahera Regency, North Maluku Province which resulted in the death of dozens of people. The purpose of this research is to apply IoT Technology and Various Sensors to design a Sea Wave Monitoring System as an Early Warning on Marine Transportation Modes which if bad weather occurs can threaten safety when doing activities at sea. The monitoring system prototype was developed to provide early information on the high danger of sea waves both through sound, sirens, and widely accessed using mobile phones and the internet. The test results of the IoT-based sea wave notification system show that this technology is effective in detecting certain wave heights, ranging from half a meter to two meters, and providing early warning quickly and accurately. The sensors integrated in the system are capable of measuring changes in wave height with high precision, and IoT technology enables stable data transmission to various communication platforms, including mobile apps and instant messaging systems. With the ability to detect various wave heights, this system can be a reliable and efficient disaster mitigation tool, and can be further developed to support better preparedness for coastal communities against the potential threat of high waves and tsunamis.